Berberrubine, a Main Metabolite of Berberine, Alleviates Non-Alcoholic Fatty Liver Disease via Modulating Glucose and Lipid Metabolism and Restoring Gut Microbiota - Yang, Sa; Cao, Shijie; Li, Congyu; Zhang, Jichao; Liu, Chang; Qiu, Feng; Kang, Ning (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a major public health problem in many countries. Berberine (BBR) is an effective therapeutic agent in alleviating NAFLD. Berberrubine (BRB) is one of the main active metabolites of BBR, which shows significant anti-obesity and anti-hypoglycemic effects. However, whether BRB, the metabolites of BBR, is responsible for the therapeutic effect of BBR in vivo and the underlying mechanism of BRB on NAFLD have not been explored. In this study, the ability of BRB to ameliorate NAFLD was investigated and the underlying mechanism was explored. The results showed that BRB treatments could significantly improve hepatic steatosis and insulin resistance in high-fat diet (HFD)-fed mice and in oleic acid (OA)-treated HepG2 cells. Meanwhile, BBR and BRB treatment similarly prevented the lipid accumulation via regulating the proteins expression of ATGL, GK, PPARα, CPT-1, ACC1, FAS and CD36. In addition, compared with BBR, BRB was capable of maintaining glucose homeostasis via GLUT2, GSK3β and G6Pase in HFD-fed mice. Additionally, the components of the gut microbiota in mice were analyzed by 16S rRNA gene sequencing. BBR and BRB treatment could greatly modify the structure and composition of gut microbiota. At the genus level, BBR and BRB treatment decreased Lactobacillus and Romboutsia, while BBR increased beneficial bacteria, such as Akkermansia and Bacteroides, and BRB increased beneficial bacteria, such as Ileibacterium and Mucispirillum. Taken together, BRB and BBR were both the active forms of BBR to alleviate NAFLD in vivo and BRB could be used as a functional material to treat NAFLD clinically.